EDUKASI DAN PEMBAGIAN MASKER SERTA HAND SANITISER SEBAGAI UPAYA PENCEGAHAN PENULARAN COVID-19. - Nurman Hidaya; Dewy Haryanti Parman; Paridah Paridah; Agus Purnamasari; Selvia Febrianti (Fakultas Ilmu Kesehatan Universitas Borneo Tarakan, 2021)
The COVID-19 pandemic requires people to change their lifestyle, implement health protocols to avoid the Covid-19 virus. The reality on the ground is that there are still people who do not comply with the existing health protocols. The purpose of this activity is to reduce the risk of the community being exposed to COVID-19 by implementing health protocols and supporting government programs in an effort to prevent the transmission of COVID-19. The method of implementing this service is through questions and answers and education through the distribution of leaflets, masks and hand sanitisers to traders and buyers. Stages of activities include the stages of preparation, implementation and evaluation carried out with. Implement health protocols. The indicator for achieving this activity is increasing public understanding and awareness in complying with health protocols.Â Keywords: Community Compliance, Health Protocol and Covid-19